Facteurs discoursifs dans I'amplification du texte pendant la traduction - Szeflińska-Karkowska, Magdalena (Wydawnictwo Naukowe UAM, 2000)
This article discusses the role of discourse’s factors in amplification in the process of translation from the French language to the Polish language. Role of discourse’s factors is discussed from the perspective of comprehension which is examined with regard to syntactic and semantic components of the text. A detailed analysis of the cognitive process involved in translation is presented on the basis of examples from literary texts.
On the role of discourse’s factors in amplification in translation